1990
DOI: 10.1177/036354659001800609
|View full text |Cite
|
Sign up to set email alerts
|

Meniscus repair in the anterior cruciate deficient knee

Abstract: From 1979 to 1986, isolated repair of a peripheral vascular zone meniscal tear was performed in 22 patients (23 menisci) who had ACL insufficiency. For various reasons none of these patients underwent repair or reconstruction of their ACL. The meniscus repair was done by open arthrotomy in 12 cases and by arthroscopic techniques in 11 cases. The purpose of this study was to evaluate the success rate of a meniscal repair in an anterior cruciate deficient knee. The average age of the patients at the time of surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 39 publications
1
20
0
2
Order By: Relevance
“…Concluíram que, mesmo que os resultados insatisfatórios sejam maiores nos pacientes com joelhos instáveis, a lesão do LCA não contraindica a reparação do menisco. Hanks et al (5) realizaram 23 reparações do menisco em joelhos instáveis, sendo 12 por artrotomia e 11 por artroscopia, e observaram nova ruptura em apenas três casos. Desses pacientes, seis referiam dor, mas só um necessitou de analgésico.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Concluíram que, mesmo que os resultados insatisfatórios sejam maiores nos pacientes com joelhos instáveis, a lesão do LCA não contraindica a reparação do menisco. Hanks et al (5) realizaram 23 reparações do menisco em joelhos instáveis, sendo 12 por artrotomia e 11 por artroscopia, e observaram nova ruptura em apenas três casos. Desses pacientes, seis referiam dor, mas só um necessitou de analgésico.…”
Section: Discussionunclassified
“…Grupo I (lesão do menisco e reparação do LCA (4) , Hanks et al (5) e Koukoulias e Papastergiou (6) os quais consideram que a instabilidade não contraindica a reparação do menisco, houve situações em que a reparação do menisco foi feita em pacientes com lesão do LCA, mas refratários a realizar a reparação ligamentar.…”
Section: Classificação Dos Indivíduosunclassified
“…Ideally, in a knee in which there is both an ACL tear and a repairable meniscal tear, the former should be reconstructed and the latter repaired [4,7,8]. However, for various reasons, some patients elect not to undergo a ligament reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study there was a failure rate of 18% (4/22) in group 2 versus 5% (1/23) in group 1. Hanks et al [8] reported a 13% failure rate of meniscal repair in the ACL-deficient knee. They concluded that even though the failure rate may be higher in an unstable knee, meniscal repair was not contraindicated in an ACL-deficient knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation